Association of acrylamide hemoglobin biomarkers with chronic obstructive pulmonary disease in the general population in the US: NHANES 2013–2016. Issue 24 (1st December 2021) - Liu, Shan; Ben, Xiaosong; Liang, Huanzhu; Fei, Qiaoyuan; Guo, Xinrong; Weng, Xueqiong; Wu, Yingying; Wen, Lin; Wang, Ruihua; Chen, Jingmin; Jing, Chunxia
Abstract : HbGA/HbAA was positively correlated with COPD, which was more concentrated in males, obese people, or people with a PIR < 1.85. HbGA/HbAA was expected to be a biomarker associated with AA exposure. Abstract : Background : Acrylamide is a well-known potential carcinogenic compound formed as an intermediate in the Maillard reaction during heat treatment, mainly from high-temperature frying, and is found in baked goods and coffee, as well as resulting from water treatment, textiles and paper processing. The effects of acrylamide on lung disease in humans remains unclear. We aimed to investigate the association between blood acrylamide and glycidamide and chronic obstructive pulmonary disease (COPD) in the United States of America (U.S.) population using PROC logistic regression models. Results : 2744 participants aged 20 to 80 from the 2013–2016 National Health and Nutrition Examination Survey (NHANES) were enrolled. After adjusting for demographic data, health factors and serum cotinine, the ratio of HbGA to HbAA (HbGA/HbAA) significantly increased the risk of COPD ( P for trend = 0.022). The odds ratio (OR) with a 95% confidence interval (95% CI) for HbGA/HbAA in the third tile was 2.45 (1.12–5.31), compared with the lowest tile. The restricted cubic spline (RCS) curve showed a positive linear correlation between the log (HbGA/HbAA) and the risk of COPD ( P = 0.030). Conclusion : The ratio of glycidamide and acrylamide (HbGA/HbAA) was associated with COPD. This association was more prominent in males, obese individuals, people with a poverty income ratio (PIR) < 1.85 or people who never exercise. However, null associations were observed between HbAA, HbGA and HbAA + HbGA, and COPD.